The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fpubh.2022.804825
|View full text |Cite
|
Sign up to set email alerts
|

Aerosols and Bacteria From Hand Washing and Drying in Indoor Air

Abstract: Effective hand drying is an important part of hand hygiene that can reduce the risk of infectious disease transmission through cross-contamination of surfaces by wet hands. However, hand drying methods may also cause aerosolisation of pathogenic microorganisms if they are present in washed hands. This study investigated experimentally the impact of washing hands and different hand drying methods on the concentration and size distribution of aerosols and bacteria in indoor air. In this experiment, aerosol and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Consequently, the water quality in turn affected the hand hygiene status of customers together with the other factors as described in Table 7. This finding is supported by the other's work as the source of water, 18 handwashing facility conditions (unavailability of soap 42 ), and customers' improper handwashing practice, 31,43 inadequate handwashing time, lack of training 5,24,44 and unavailability of poster demonstration on good handwashing practice, inappropriate method of hand drying 34,45,46 and method of fetching water from the container 32 had an association with the effectiveness of handwashing practice in the removal of pathogens from hands thereby hand hygiene status.…”
Section: Discussionmentioning
confidence: 91%
“…Consequently, the water quality in turn affected the hand hygiene status of customers together with the other factors as described in Table 7. This finding is supported by the other's work as the source of water, 18 handwashing facility conditions (unavailability of soap 42 ), and customers' improper handwashing practice, 31,43 inadequate handwashing time, lack of training 5,24,44 and unavailability of poster demonstration on good handwashing practice, inappropriate method of hand drying 34,45,46 and method of fetching water from the container 32 had an association with the effectiveness of handwashing practice in the removal of pathogens from hands thereby hand hygiene status.…”
Section: Discussionmentioning
confidence: 91%
“…Most previous studies on handwashing have been conducted among health professionals and students, primarily focusing on knowledge ( 19 , 20 ). Although there have been reports ( 21 ) on food hygiene among university students, to our knowledge, hand hygiene education utilizing objective indicators such as the ATP test has not been implemented in elementary schools.…”
Section: Discussionmentioning
confidence: 99%
“…Effective hand drying reduces cross-contamination compared to dry hand by touching surfaces [11][12][13] . However, the hand dryer itself can be a source of contamination and disperses microorganism through aerosol particles 14,15 .Substantial articles have investigated the hygienic effects of hand dryers. Suen et al 8 indicated that drugresistant bacteria could be found in 52 types of bacteria species on hand-drying facilities in public washrooms, and Huesca et al 9 demonstrated that hand dryers were related to the bacterial deposition on hand surfaces and the movement of polluted air, and might even be a cause for the dispersion of infectious bacteria.…”
mentioning
confidence: 99%
“…Effective hand drying reduces cross-contamination compared to dry hand by touching surfaces [11][12][13] . However, the hand dryer itself can be a source of contamination and disperses microorganism through aerosol particles 14,15 .…”
mentioning
confidence: 99%